EFEKTIVITAS PENINDAKAN TERHADAP PIHAK YANG MENEMPATI RUMAH DINAS DILUAR JANGKA WAKTU YANG DITENTUKAN (STUDI DI KABUPATEN KETAPANG) - NIM. A1011191018, CARMENITA SONIA (Fakultas Hukum Universitas Tanjungpura, 2023)
Abstract Official houses are performance and inventory support facilities lent by the state during the working period depending on the group of official houses occupied. The existence of employees who occupy official houses outside the loan period is a violation. For violations committed blatantly, it can cause unwanted things, including legal issues involving the rights and obligations of users with local governments. The formulation of the problem in this study is